2021
DOI: 10.3390/ijms22052291
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Inflammation and Dysfunction in Lupus-Prone Mice-IL-6 as Mediator of Disease Initiation

Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease and patients are under an increased risk for cardiovascular (CV) events and mortality. The increased CV risk for patients with SLE seems to be caused by a premature and accelerated atherosclerosis, attributable to lupus-specific risk factors (i.e., increased systemic inflammation, altered immune status), apart from traditional CV risk factors. To date, there is no established experimental model to explore the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Cytokine dysregulation aggravates immune dysfunction, leading to autoimmune diseases such as SLE [ 33 ]. The pro-inflammatory cytokines, which infer IL-6 as a mediator of disease initiation, increase the susceptivity of the vascular pathology in MRL-Fas lpr mouse model [ 34 ]. A meta-analysis suggested that the levels of IL-6 and TNF- α in SLE patients were higher than in healthy controls [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine dysregulation aggravates immune dysfunction, leading to autoimmune diseases such as SLE [ 33 ]. The pro-inflammatory cytokines, which infer IL-6 as a mediator of disease initiation, increase the susceptivity of the vascular pathology in MRL-Fas lpr mouse model [ 34 ]. A meta-analysis suggested that the levels of IL-6 and TNF- α in SLE patients were higher than in healthy controls [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the proliferation of B-GCs by PRL also resulted in an increase in the percentage of IL6+ cells, and elevated concentrations of IL-6 in the serum of mice and supernatants of differentiated B-GCs correlated with high PRL concentrations. IL-6 serum levels are markedly increased in mice with autoimmunity ( 25 , 49 ), and human patients with SLE ( 50 , 51 ). IL-6 is required for the GC formation because it facilitates the expression of master regulator BCL6 in helper follicular T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is also a common characteristic of the two conditions and is found in particular in the composition of each in the form of a pro-inflammatory intestinal environment, which leads to an expansion of gliadin-specific T cells (in people with genetic sensitivity) and the perpetuation of a pro-inflammatory phenotype in the case of CD, or, on the contrary, of a vascular inflammation mediated by IL-6 found in SLE, which has as a consequence the appearance of perivascular and vascular leukocyte infiltration and vascular dysfunction with the implicit increase in cardiovascular mortality [28,29].…”
Section: Celiac Diseasementioning
confidence: 99%